Getting elected is the easy part : working and winning in the state legislature - Keiser, Karen (Basalt Books, 2023)
Across the nation every two years, first-time lawmakers enter state legislatures--institutions steeped in tradition, arcane procedures, and unwritten rules. Although dozens of publications advise candidates on how to run and win campaigns, for those elected, few resources exist. After more than twenty years in the Washington State Legislature, Senator Karen Keiser realized she could address that knowledge gap. Written for legislative newcomers and others interested in state government, her book blends documented research with her personal experiences and observations about how to succeed and achieve real change. She focuses on the culture adjustment and challenges many newly elected lawmakers face, and offers tips and advice to help them achieve their legislative goals.